Perancangan Poster Carousel Sebagai Media Dakwah Berbasis Digital (International Forum of Researchers and Lecturers, 2025)
In the continuously evolving digital era, preaching media is becoming increasingly vast and dynamic. One medium with significant potential is digitally-based posters. This research aims to identify and analyze the design strategies for digital-based posters as an effective medium for preaching. Through a qualitative approach and design study, the authors explore various design aspects, including the selection of illustrations, typography, and color that influence the success of the preaching message.